Analyzing the EU sovereign debt crisis by a new asymmetric copula with reversible correlations. Issue 56 (2nd December 2022) - Kobayashi, Masahito; Chen, Jinghui
ABSTRACT: It is well known that a correlation between stock and bond returns had changed in the financial crisis. This paper analyzes it using a novel asymmetric copula. The proposed test is constructed from bivariate split normal distribution and can change correlation signs of upper and lower tails of distribution independently. It is shown that the stock–bond correlation of the EU periphery countries in the capital outflow period is asymmetric, in that it is higher in the lower tail than in the upper tail. The lower tail correlation is higher when capital outflowed than in the calm period. The lower tail correlation sign in the inflow period was at odds; Ireland, Italy and Spain had negative lower tail correlation. The correlation reversion of these three countries can be explained by the change of capital movement from inflow to outflow. In contrast, Germany had negative stock–bond correlation before and after the crisis.